El cuento en el desarrollo de la oralidad en niños de segundo año de EGB de la Unidad Educativa Vigotsky, en el periodo 2020-2021 - Bonilla Concha, Estefanny María (2021)
The present research work has as its theme: "The story in the development of orality in children of second year of GBE of the educational unit "Vigotsky", in the period 2020-2021", whose purpose was to analyze the story as a methodological tool, with the objectives of characterizing the level of oral development through the application of the story, determine the process for the development of orality and the elaboration of workshops that develop orality. The methodology has a qualitative approach; since it focuses on understanding the fundamental aspects regarding orality, it has a non-experimental design due to the fact that none of the variables will be intervened. The exploration was carried out with 24 students who make up the 2nd grade of EGB and 4 teachers who tutor them, the instruments used for the collection of information from the students are an observation sheet with parameters to evaluate the most important aspects of orality after the application of the story and the communicative competencies that the student requires to improve their learning abilities and the instruments used for the collection of information from the teachers were a survey to know the usefulness of the use of the story in the development of orality in the teaching staf. These results show that the story is an element that has a positive influence on orality, although there are still deficiencies in its work as such.